A study of morbidity and mortality profile among preterms suffering from Hyaline Membrane Disease in a tertiary care hospital in Cuttack, India - Pattar, Mounesh; Das, Leena (International Journal of Contemporary Pediatrics, 2018)
Background: Every newborn carries within itself immense possibility to transform into a complete healthy human being and fulfill the needs the future will demand. Of the problems of premature baby, respiratory causes are the commonest admission to NICU. The common respiratory problem encountered is Respiratory distress syndrome (RDS) also known as Hyaline membrane disease (HMD), whose incidence increases as babies are born early. The objective of the study was to assess the morbidity and mortality profile among preterms suffering from Hayaline membrane disease in a tertiary care hospital in Cuttack. Methods: A prospective comparative study was conducted in the neonatal intensive care unit of SVPPGIP Hospital attached to the SCB Medical College, Department of Pediatrics, Cuttack from September 2010 to September 2012. A total of 103 preterm newborn with Hyaline membrane disease were included in the study. Results: Out of 103, 67 male and 36 females were included in the study. The total neonatal death in our study was 44 (42.7%) pre-term out of 103 subjects. The death of neonate within 1st week or 168 hrs of age of birth irrespective of cause was considered for early neonatal death which was 21 (47.7%) of the total neonatal death. Conclusions: It may be worth considering surfactant replacement therapy in neonates between with RDS 30-33 weeks gestation in level III care setup in our country even being referred late but less than 24 hrs of age with supportive and aseptic care.